DEEP FIBROMATOSIS (DESMOID TUMOR) IN THE TRUNK AND ABDOMEN: CT/MRI AND PATHOLOGICAL FINDINGS - YAMRUBBOON, Wichchuda; PHONGKITKARUN, Sith; JAOVISIDHA, Suphaneewan; SIRIKULCHAYANONTA, Vorachai; TAPANEEYAKORN, Jiemjit (The ASEAN Journal of Radiology, 2023)
Objective: To describe imaging findings (Computerized Tomography [CT]/ Magnetic Resonance Imaging [MRI]) correlated with pathological findings, of the deep fibromatosis (desmoid tumor) in the trunk and abdomen. Material and methods: We retrospectively reviewed such cases in Ramathibodi hospital from January 2001 to December 2005, who had CT/MRI imaging along with pathological slices available. Results: Seven cases were enrolled in the study ; four of 7 had CT examinations and the other 3 had MR imaging. The locations were extra-abdominal (n=4), intra-abdominal (n=2), and abdominal-wall desmoid tumor (n=1). The margins were well-defined (n=3), partially well-defined (n=3), and ill-defined (n=1). On CT, they were iso- or hypodense. On MRI, although the lesions were iso- to hypointense-T1 and heterogeneously hyperintense-T2 ; there were ill-defined areas of hypointensity in both T1 and T2-weigthed images that was the signal of fibrous tissue. Most lesions showed moderate to strong enhancement after IV contrast injection. Histology showed area of spindle cells in dense collagen fiber, with small & large slitlike vessels. There was no nuclear atypia in majority. Conclusion: Deep fibromatosis (desmoid tumor) has nonspecific CT findings. In MRI, identifying area of hypointensity on both T1WI and T2WI, with varying degree of enhancement after Gadolinium injection, helps in the diagnosis of the nature of fibrous-origin tumors.